Proteomic Profiling and Clinical Insights: The Role of MMP9 in Differentiating Psoriasis Vulgaris from Generalized Pustular Psoriasis - Gong T; Chen J; Xiao Z; Luo R; Tong Z; Ke H; Liu Z; Xiao C; Xiang N; Ji C (Journal of Inflammation Research)
Ting Gong,1,* Jiawen Chen,2– 4,* Zhixun Xiao,2– 4,* Renwei Luo,2– 4 Zequn Tong,2– 4 Hui Ke,2– 4 Zhao Liu,2,5 Cuirong Xiao,2,6 Niu Xiang,2– 4 Chao Ji2– 4 1Central Laboratory, the First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350000, People’s Republic of China; 2Department of Dermatology, The First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350000, People’s Republic of China; 3Key Laboratory of Skin Cancer of Fujian Higher Education Institutions, Fuzhou, Fujian, 350000, People’s Republic of China; 4Fujian Provincial Clinical Research Center for Immune Skin Diseases, the First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350000, People’s Republic of China; 5Department of Dermatology, Affiliated Hospital of Hebei University of Engineering, Handan, Hebei, 056000, People’s Republic of China; 6Department of Dermatology, Zhangzhou Affiliated Hospital of Fujian Medical University, Zhangzhou, Fujian, 363000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Niu Xiang, Department of Dermatology, the First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350000, People’s Republic of China, Email 408089668@qq.com Chao Ji, Department of Dermatology, the First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350000, People’s Republic of China, Email jichaofy@fjmu.edu.cnBackground: Generalized pustular psoriasis (GPP) constitutes a rare, severe inflammatory disorder that differs from psoriasis vulgaris (PV). The IL-36 pathway has been identified as a key element in GPP pathogenesis.Objective: To explore protein expression between PV and GPP, providing insights into potential mechanisms.Methods: We performed proteomic analysis of tissue specimens from patients with PV and GPP to identify differentially expressed proteins. Comparative analysis of the proteomic data was performed and proteins with significant differences were further identified using immunofluorescence and Western blot techniques. Differential proteins were also explored by evaluating the efficacy of IL-36R inhibitors before and after GPP treatment, providing potential avenues for targeted therapeutic strategies.Results: Tissue proteomic profiling showed that matrix metallopeptidase 9 (MMP9) increased significantly in the GPP as compared to PV. Immunofluorescence and Western blot analysis confirmed that MMP9 is higher expressed in GPP. And after therapy with IL-36 inhibitors showed that the level of MMP9 expression was markedly reduced.Conclusion: MMP9 may be involved with the pathogenesis of GPP.Keywords: generalized pustular psoriasis, psoriasis vulgaris, IL-36R inhibitors, matrix metallopeptidase 9, proteomics profiling